INDUKSI TRIPLOID IKAN SELAIS (Kryptopterus lympok) MENGGUNAKAN KEJUTAN PANAS - Alawi, Hamdan; Nuraini, Nuraini; Sapriana, Sapriana (Jurnal Perikanan dan Kelautan, 2009)
A study was conducted to induced triploidy in fertilized egg of sheatfishlarvae , (Kryptopterus lympok) using heat shock. The eggs were exposed at 40OCfor shock duration of 1 , 3 , 5 and 0 minutes as a diploid control. Results showedthat the 5 minutes shock duration was the highest triploid induction and yield(91.7 and 62.9%). Erythrocyte analysis showed that the volume of triploid fishgroup was bigger that that of diploid one. The fertilization, hatching and survivalrate was lower in triploid groups, while SGR was higher compared to diploid fish.